FoxP3(+) Regulatory T Cells Attenuate Experimental Necrotizing Enterocolitis - Dingle, Bridgette M. (Public Library of Science, 2013)
Necrotizing enterocolitis (NEC) results from severe intestinal inflammation in premature infants. FoxP3(+) regulatory T cells (Tregs) are central to gut homeostasis. While Treg proportions are significantly reduced in the ileums of premature infants with NEC, it is unknown whether they play a critical function in preventing NEC. This study investigated Treg development in newborn rat pups and their role in experimental NEC induction. Utilizing an established rat model of experimental NEC, the ontogeny of T cells and Tregs in newborn pups was characterized by flow cytometry. To investigate the functions of Tregs, newborn pups were given Tregs harvested from adult rats prior to NEC induction to assess clinical improvement and mechanisms of immune regulation. The results revealed that there were few Treg numbers in the terminal ileums of newborn rats and 8-fold reduction after NEC. Adoptive transfer of Tregs significantly improved weight loss, survival from 53% to 88%, and NEC incidence from 87% to 35%. The Tregs modulated the immune response as manifested in reduced CD80 expression on antigen presenting cells and decreased T cell activation within the mesenteric lymph nodes. These findings suggest that while Tregs are present in the intestines, their numbers might be insufficient to dampen the excessive inflammatory state in NEC. Adoptive transfer of Tregs attenuates the severity of NEC by limiting the immune response. Strategies to enhance Tregs have a therapeutic potential in controlling the development of NEC.